Evaluation of serum vitamin D metabolites, phagocytosis, and biomarkers of inflammation in dogs with naturally occurring diabetes mellitus - Jaffey, Jared A.; Backus, Robert C.; Kreisler, Rachael; Graves, Thomas K.; Al-Nakkash, Layla; Allison, Lauren (Frontiers in Veterinary Science, 2024)
Naturally occurring diabetes mellitus (NODM) is one of the most common endocrine disorders in dogs and its etiology closely resembles type 1 diabetes mellitus (T1DM) in people. Human patients with T1DM commonly have cellular derangements consistent with inflammation, impaired immune function, and hypovitaminosis D. There is little information available regarding inflammatory biomarkers, immune function, and vitamin D status in diabetic dogs. Therefore, our objectives were to assess inflammatory biomarkers, vitamin D metabolites, and phagocytic capacity in diabetic dogs and determine whether associations exist with these variables and the level of clinical control or vitamin D metabolites. This was a prospective case–control study that included 20 otherwise healthy diabetic dogs (clinically controlled, n = 10; uncontrolled, n = 10) and 20 non-diabetic, healthy, age (± 2 years), breed, and sex matched controls. Complete blood count, biochemical panel, urinalysis, and fructosamine were performed at a single commercial reference laboratory. Basal plasma tumor necrosis factor (TNF)-α, interleukin (IL)-6, IL-8, and IL-10 were measured using a canine-specific multiplex bead-based assay. Serum C-reactive protein (CRP) was measured using a commercially available ELISA kit. Serum 25-hydroxyvitamin (OH)D3 and 24,25-dihydroxyvitamin (OH)2D3 were measured with HPLC. Phagocytosis of opsonized-Escherichia coli (E. coli) was evaluated with flow cytometry. Diabetic dogs had higher serum CRP concentrations than controls (p = 0.02). Plasma IL-8 concentrations were higher in diabetic dogs with uncontrolled clinical disease compared to controls (p = 0.02). Diabetic dogs had a lower percentage of leukocytes that phagocytized opsonized-E. coli (p = 0.02), but an increased number of bacteria phagocytized per cell (p < 0.001) compared to controls. No between-group differences were identified in vitamin D metabolites, nor were associations found between vitamin D and any variables. Fructosamine had a positive association with serum CRP concentration (rho = 0.35, p = 0.03) and number of bacteria phagocytized per cell (rho = 0.45, p = 0.004) in our cohort (n = 40). Like people with T1DM, diabetic dogs have a proinflammatory phenotype and phagocytic dysregulation that may be correlated with glycemic control.